2007
DOI: 10.1038/nm1545
|View full text |Cite|
|
Sign up to set email alerts
|

Aldosterone impairs vascular reactivity by decreasing glucose-6-phosphate dehydrogenase activity

Abstract: Hyperaldosteronism is associated with impaired vascular reactivity; however, the mechanisms by which aldosterone promotes endothelial dysfunction remain unknown. Glucose-6-phosphate dehydrogenase (G6PD) modulates vascular function by limiting oxidant stress to preserve bioavailable nitric oxide (NO(*)). Here we show that aldosterone (10(-9)-;10(-7) mol/l) decreased endothelial G6PD expression and activity in vitro, resulting in increased oxidant stress and decreased NO(*) levels-similar to what is observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
261
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(278 citation statements)
references
References 51 publications
15
261
0
2
Order By: Relevance
“…Dichlorodihydrofluorescein Fluorescence-ROS generation was assessed using 6-carboxy-2Ј,7Ј dichlorodihydrofluorescein diacetate ester fluorescence (5 mol/liter) (Molecular Probes) as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichlorodihydrofluorescein Fluorescence-ROS generation was assessed using 6-carboxy-2Ј,7Ј dichlorodihydrofluorescein diacetate ester fluorescence (5 mol/liter) (Molecular Probes) as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…In the vascular endothelium, aldosterone has been shown to promote endothelial dysfunction by inducing an acquired antioxidant-deficient state that disrupts cellular redox homeostasis to increase ROS accumulation and diminish NO ⅐ levels. In vivo, this results in diminished endothelium-dependent vascular reactivity (7). The relationship between aldosterone-induced oxidant stress and NO ⅐ -stimulated vasodilatory signaling pathways in VSMC, however, remains unknown.…”
mentioning
confidence: 99%
“…120 Finally, it has been shown that aldosterone induces a G6PD-deficient phenotype that can be improved by aldosterone antagonist or gene transfer of G6PD. 121 Of great interest, it has recently been suggested that, similar to what has been described in the heart, brain and vasculature, 122 the eye has a dynamic aldosterone-mineralocorticoid receptor system that has an important pathophysiological role in the development of retinal pathology. Wilkinson-Berka et al 123 , using a rat model of oxygen-induced retinopathy (OIR) that has features of premature retinopathy in humans with neovascularization, have shown that mineralocorticoid receptor antagonism with spironolactone improves retinal angiogenesis by attenuating leukostasis and decreasing proinflamatory responses.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 97%
“…A recent report indicates that aldosterone induces a downregulation of endothelial glucose-6-phosphate dehydrogenase that results in impaired oxidative stress and decreased NO availability. Interestingly, these effects of aldosterone were completely prevented by spironolactone (31). In support to this, we have recently shown that spironolactone completely prevented renal acute injury induced by ischemia-reperfusion by a mechanism that involved preservation of renal plasma flow, reestablishment of urinary NO 2 /NO 3 excretion that was accompanied by increased expression of eNOS and phosphorylation at its residue S1177, as well as by a reduction of lipoperoxidation and cell apoptotic death, indicating indeed that aldosterone also participates in hypoperfusion observed in this model (36).…”
Section: Role Of Aldosterone In Csa Nephrotoxicitymentioning
confidence: 98%